Carcass Quality of 75 Days Kampung Unggul Balitnak Chickens Fed Diets With Fermented Cassava Leaf Flour (Manihot Utilissima) - Untung Pardosi; Ghuido Martinus (Talenta Publisher, 2024)
The advantage of Kampung Unggul Balitnak Chickens chicken is that the harvest period is shorter than ordinary native chicken. This study aims to determine the effect of fermented cassava leaf flour (Manihot Utilissima) in commercial fed on the quality of carcasses of Kampung Unggul Balitnak chickens aged 75 days. The research method used was a complete randomized design (CRD) with 4 treatments consisting of P0 = 100% commercial ration + 0% fermented cassava leaf flour, P1 = 98% commercial ration + 2% fermented cassava leaf flour, P2 = 96% commercial ration + 4% fermented cassava leaf flour, P3 = 94% commercial ration + 6% fermented cassava leaf flour with 5 replicates. Parameters observed included slaughter weight, carcass weight and carcass percentage. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that the provision of fermented cassava (Manihot Utilissima) leaf meal in commercial rations on 75-day-old KUB chickens had no significant effect (P>0.05) on slaughter weight, carcass weight and carcass percentage. In conclusion addition of fermented cassava flour in commercial fed did not effect carcass quality thus 6% of fermented cassava flour could be used as an additional ingredients in commercial rations.